Determinants of Capital Structure: An empirical study of UK firms - Chen, Lujie (2007)
Capital structure has been one of the most controversial issues in the ground of finance during past years. There are a number of existing theories and empirical studies observing patterns involved in choosing a capital structure, however until now, there is no universal one. With the objective to provide an insight into determinants influence a firm's level of debt, we apply ANOVA and multiple regression analysis of secondary data on 80 UK public companies operating in 10 industries. In addition, the study on the impacts of revised IAS 19 on pension deficit makes this dissertation differentiated from existing ones. We divide the time span into pre-pension scheme period 2001-2004 and post-pension scheme 2005-2006 to examine how the adjustment at balance sheet affects firm's capital structure.